PENYULUHAN DAN PENERAPAN TEKNOLOGI RECIRCULATING AQUACULTURE SYSTEM (RAS) UNTUK PENGELOLAAN KUALITAS AIR DAN KESEHATAN IKAN LELE PADA POKDAKAN BINTANG ROSELA JAYA DI DESA PATOMAN, KABUPATEN PRINGSEWU, PROVINSI LAMPUNG - Sarida, Munti; Setyawan, Agus; Sulistiono, Wahyu Eko; Alfina, Ria; Azizah, Azizah (Jurnal Abdi Insani, 2024)
Significant challenges encountered in the catfish farming production at Pokdakan Bintang Rosela Jaya are largely influenced by water quality issues, particularly the elevated levels of ammonia in the pond water and delays in water replacement management. This community service initiative aims to enhance the knowledge and skills of the members of Pokdakan regarding the implementation of Recirculating Aquaculture System (RAS) technology in catfish farming. The methodology for this community service project comprises several stages, including site surveys and assessments of the partner's pond conditions, educational outreach on water quality management and fish health, the design and installation of RAS technology, and the evaluation of the outreach outcomes. The site survey revealed that the catfish farming activities were facing significant water quality challenges. The educational outreach, attended by 20 participants on August 10, 2024, covered essential topics such as the importance of water quality management, the application of RAS technology, fish health management, and an introduction to common diseases affecting catfish. Evaluation results indicated a notable increase in participants' knowledge, with average pre-test scores rising from 36 to 46 following the outreach. This initiative is anticipated to assist partners in addressing water quality issues, improving fish health, and promoting sustainable catfish farming practices. Consequently, the effective implementation of RAS technology is expected to yield long-term benefits for the success of catfish farming at this Pokdakan.